Association of Bone Metabolism Biomarkers with Infant Linear Growth in a Birth Cohort from Dhaka, Bangladesh (P10-012-19). (13th June 2019) - Qamar, Huma; Onoyovwi, Akpevwe; Mahmud, Abdullah Al; Ahmed, Tahmeed; Bandsma, Robert; Roth, Daniel
Abstract: Objectives: To estimate the associations of venous cord, infant 3-month, and 6-month bone-related biomarker concentrations (amino-terminal propeptide of C-type natriuretic peptide [NT-proCNP], fibroblast-like growth factor 21 [FGF21], receptor activator of nuclear activator kappa-b ligand [RANKL], osteoprotegerin [OPG], 25-hydroxyvitamin D [25OHD], FGF23, osteocalcin [OC], and insulin-like growth factor 1 [IGF-I]) with infant length-for-age z-score (LAZ) trajectories from 0 to 12 months of age, in Dhaka, Bangladesh. Methods: This was a sub-study of the Maternal Vitamin D for Infant Growth trial in Dhaka, Bangladesh. NT-proCNP, FGF21, FGF23, and IGF-I were measured by ELISA, 25OHD by HPLC-tandem mass spectrometry, and OC, OPG, and RANKL by Milliplex magnetic panels. The primary outcome was LAZ from birth to 12 months of age. Among eligible infants ( n  = 569), associations between each biomarker and LAZ were estimated by linear mixed-effects models with restricted cubic splines. Significant biomarker-age interaction terms were interpreted as evidence of associations of the biomarker with postnatal growth (PG) trajectory. Marginal effects at discrete ages were estimated based on the fitted model. Results: 25OHD was associated with PG ( P  = 0.022), with a negative association with LAZ at birth, but no association at subsequent time points. IGF1 and RANKL were both significantly associated with PG (pIGF1  < 0.001; pRANKL  = 0.022), were not associated with LAZ at birth, but were positively associated with LAZ at subsequent time points. OC was associated with PG ( P  < 0.001), was negatively associated with LAZ at birth, and was positively associated with LAZ at 12 months. NT-proCNP was associated with postnatal LAZ trajectories ( P  < 0.001), with negative associations with LAZ at 3 and 6 months of age, but no association at 12 months. There was no significant association between FGF21 and PG; however, FGF21 was consistently negatively associated with LAZ. OPG and FGF23 were not associated with PG. Conclusions: Several serum/plasma biomarkers were associated with infant linear growth in a cohort from Bangladesh. IGF1, RANKL, and OC were most strongly associated postnatal LAZ growth. FGF21 was not associated with PG but was associated with fetal linear growth with sustained effects in the postnatal period. Funding Sources: Funded by the Bill and Melinda Gates Foundation.